Effect of Lactobacillus plantarum Concentration Level on Physicochemical Properties of Fermented Goat Meat Dendeng. Issue 1 (April 2020) - Radiati, L E; Umam, A K; Susilo, A; Thoifi, A A
Abstract: This research aimed to determine the effect of Lactobacillus plantarum on the manufacturing process of fermented goat meat dendeng. The completely randomized design with four treatments and four replications was applied to determine the moisture content, water activity (AW), protein content, dissolved protein content, and protein profile as physicochemical quality indicators. The level of Lactobacillus plantarum was 0 ml (T0), 0.3 ml (T1), 3 ml (T2), and 30 ml (T3), respectively. The obtained result was analyzed with SPSS for windows 16 then followed with Duncan's Multiple Range Test. The highly significant result (P<0.01) was shown on Aw, with valued at 0.61 – 0.70, moisture content at 44.24 – 46.65%, protein content at 31.98 – 38.70%, and dissolved protein content at 3.55 – 4.21%; while the molecular weight of protein profile was ranged from 16.69 to 143.54 kDa, and showed an unreadable protein band on T0, six protein bands on T1, seven protein bands on T2, and eight protein bands on T3, respectively.